KEMAMPUAN MUSIKALITAS PADA SISWA SEKOLAH DASAR KANAAN GLOBAL SCHOOL DI KOTA JAKARTA - Monica, monica (2022)
One of the goals of education is to educate the nation's life. Intelligence itself is a cognitive ability that is inseparable from the activities of the human mind, one of the things that distinguishes humans from other living things is their intelligence. Howard gardner suggests that humans have nine intelligences, in this study will discuss musical intelligence. This research is important because musical ability is an innate ability inherent in children and has existed since humans were born. This study uses a descriptive survey method with a quantitative approach. This research was motivated by the Kanaan Global School elementary school in the city of Jakarta which has its own uniqueness in learning the art of music. This study uses a musical test instrument with four indicators such as imitating the tone, imitating the rhythm, imitating the melody and responding to the rhythm. The results of this study indicate that the level of musical ability of students is categorized as musical enough (CM) as many as 44 students (31%), the level of musical ability of students is categorized as musical (M) as many as 74 students (53%) and the level of musical ability is categorized as very musical (SM). as many as 22 students (16%). Thus, we can conclude that the majority of Kanaan Global School elementary school students in Jakarta City are categorized as Musical with a total of 74 students (53%) out of 140 students in total. Keywords: Intelligence, Musicality, Music Education,Learning.